1997
DOI: 10.1115/1.2788918
|View full text |Cite
|
Sign up to set email alerts
|

A Tensegrity Structure With Buckling Compression Elements: Application to Cell Mechanics

Abstract: A tensegrity structure composed of six slender struts interconnected with 24 linearly elastic cables is used as a model of cell deformability. Struts are allowed to buckle under compression and their post-buckling behavior is determined from an energy formulation of the classical pin-ended Euler column. At the reference state, the cables carry initial tension balanced by forces exerted by struts. The structure is stretched uniaxially and the stretching force versus axial extension relationships are obtained fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 16 publications
3
69
0
Order By: Relevance
“…resist shape distortion (Ingber, 1993(Ingber, , 1998. Results of static numerical analysis using a tensegrity structure to model a cell's static properties which were in agreement with biological experimental measurements have been reported (see Stamenovic et al, 1996;Coughlin and Stamenovic, 1997).…”
Section: Introductionsupporting
confidence: 55%
“…resist shape distortion (Ingber, 1993(Ingber, , 1998. Results of static numerical analysis using a tensegrity structure to model a cell's static properties which were in agreement with biological experimental measurements have been reported (see Stamenovic et al, 1996;Coughlin and Stamenovic, 1997).…”
Section: Introductionsupporting
confidence: 55%
“…A more recent formulation of the model includes, for example, semiflexible struts analogous to microtubules, rather than rigid compression struts, and incorporates values for critical features of the individual cytoskeletal filaments (e.g. volume fraction, bending stiffness and cable stiffness) from the literature (Coughlin and Stamenovic, 1997;Stamenovic and Coughlin, 1999). This more refined model is qualitatively and quantitatively superior to that containing rigid struts.…”
Section: Mathematical Formulation Of the Tensegrity Theorymentioning
confidence: 94%
“…Largely through the work of Stamenovic and co-workers, this oversimplified micromechanical model continues to be progressively modified and strengthened over time (Coughlin and Stamenovic, 1997;Coughlin and Stamenovic, 1998;Stamenovic and Coughlin, 1999;Stamenovic and Coughlin, 2000;Stamenovic and Ingber, 2002). A more recent formulation of the model includes, for example, semiflexible struts analogous to microtubules, rather than rigid compression struts, and incorporates values for critical features of the individual cytoskeletal filaments (e.g.…”
Section: Mathematical Formulation Of the Tensegrity Theorymentioning
confidence: 99%
“…Such a behavior has been attributed to the structural properties of the CSK considering that the overall mechanical properties of the CSK are strongly related to the spatial rearrangement of the CSK-filaments (Ingber & Folkman, 1989;Ingber, 1997Ingber, , 1998Ingber & Jamieson, 1985;Ingber & Karp, 1991;Wang & Ingber, 1994) and thus can be advantageously explained by the tensegrity concept (Ingber, 1993(Ingber, , 1998Ingber et al, 1994Ingber et al, , 1995Wang & Ingber, 1994;Wendling et al, 1999Wendling et al, , 2000a. Theoretical descriptions of tensegrity structure at the cellular level have been initially given by Stamenovic's group (Coughlin & Stamenovic, 1997Stamenovic et al, 1996), whereas other theoretical studies have provided normalized predictions of the mechanical behavior which all confirmed the expected nonlinear and pre-stress-dependent behaviors (Wendling et al, 1999(Wendling et al, , 2000a. Noteworthy, the tensegrity models proposed up to now to describe the CSK response have only been studied in terms of pure elastic behavior, i.e.…”
mentioning
confidence: 98%